Existence for Time-Fractional Semilinear Diffusion Equation on the Sphere - N. D. Phuong; Ho Duy Binh; Ho Thi Kim Van; Le Dinh Long (Advances in Mathematical Physics)
Fractional diffusion on the sphere plays a large role in the study of physical phenomena customs and meteorology and geophysics. In this paper, we examine two types of the sphere problem: the initial value problem and the end value problem. We are interested in focus on the solution existence in a local or global form. In order to overcome difficult evaluations when evaluating, we need some new techniques. The main analytical tool is the use of the Banach fixed point theorem.